2020
DOI: 10.1002/alz.046615
|View full text |Cite
|
Sign up to set email alerts
|

ApoE ε4 status in pre‐dementia risk states, mild behavioural impairment and subjective cognitive decline, and the risk of incident cognitive decline

Abstract: Background Dementia has an increasing global burden with over 40 million affected individuals. With sub‐optimal advances in drug development, there is an increasing shift to determine risk of dementia in the non‐demented population. Assessment of neuropsychiatric symptoms (NPS) may offer an opportunity to capture the at‐risk group earlier. Mild Behavioural Impairment (MBI) is a validated neurobehavioural syndrome, characterized by the emergence of sustained NPS in older adults as an at‐risk state for dementia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In a recent study of National Alzheimer Coordinating Center data, the combination of informantreported MBI and subjective cognitive decline (SCD) had a greater risk of incident cognitive and functional decline at 3 years compared to either MBI or SCD alone (Ismail et al, 2021). Further, in a subsequent study, those with SCD and MBI together had a shorter median time to incident MCI compared to those with SCD in the absence of MBI (Nathan et al, 2020). Taken together the results suggest that individuals with subtle neuropsychological test score differences and MBI together may be at higher risk for cognitive and functional decline.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study of National Alzheimer Coordinating Center data, the combination of informantreported MBI and subjective cognitive decline (SCD) had a greater risk of incident cognitive and functional decline at 3 years compared to either MBI or SCD alone (Ismail et al, 2021). Further, in a subsequent study, those with SCD and MBI together had a shorter median time to incident MCI compared to those with SCD in the absence of MBI (Nathan et al, 2020). Taken together the results suggest that individuals with subtle neuropsychological test score differences and MBI together may be at higher risk for cognitive and functional decline.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with the previous literature 169 , cases are over-represented in clinical versus community samples. Longitudinal cohorts have demonstrated associations between MBI and cognitive decline, incident MCI, and incident dementia 160,162,167,170,171 and MBI has also been linked to known dementia markers, including Aβ 172,173 , tau 174,175 , white matter atrophy 176 , grey matter atrophy 177 , plasma neurofilament light 178 and AD risk loci 179,180 .…”
Section: Mild Behavioural Impairmentmentioning
confidence: 99%
“…In a recent study of National Alzheimer Coordinating Center data, the combination of informant-reported MBI and subjective cognitive decline (SCD) had a greater risk of incident cognitive and functional decline at three years compared to either MBI or SCD alone 24 . Further, in a subsequent study, those with SCD and MBI together had a shorter median time to incident MCI compared to those with SCD in the absence of MBI 48 . Taken together the results suggest that individuals with subtle neuropsychological test score differences and MBI together may be at higher risk for cognitive and functional decline.…”
Section: Discussionmentioning
confidence: 83%